Competencies of Human Resource Professionals in the Private Sector of Mongolia: A Pair-Designed Investigation and Comparison with the Global Norm - Enkhjav, Tumentsetseg; Imola, Csehne Papp; Erika, Varga (International Journal of Publication and Social Studies, 2020)
Mongolia is defined as one of the 3G /Global Growth Generators/ countries and is predicted to generate high growth and profitable investment opportunities over the next 30 years due to its growing young generation and natural resource. Even though Mongolia has increasing development in economy and business, very limited numbers of studies have been published to reveal the economic and management situations in this country. To contribute to closing this gap, the main purpose of this study was to understand the management, especially the field of human resources (HR). This sub management field is immature and has a history less than twenty years in Mongolia. In addition, , the researcher examined HR competencies in Mongolia based on the Human Resource Competency Study (HRCS) model 2012 which is composed of six HR competencies namely: strategic positioning, credible activist, capability builder, change champion, HR innovator, and technology proponents. Furthermore, the local HR competency result was compared with global norms which were identified by the RBL group in 2012. The pair design was carried out, and a total of 200 data has complied from both HR managers as well as employees from 50 private companies in Mongolia. Based on the 5-point Likert scale, local competence levels ranged from 3.5 to 3.8. The results of this study showed that local competency levels were lower than the HR global norms.